The Resilience of Russia's Oil and Gas Exports Against International Sanctions (2022–2023) - Muhammad Gibran Humam Fadlurrahman; Yogi Susatyo; Zeffry Alkatiri (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2025)
Russia faced embargo sanctions from the United States, the European Union and its allies during the Russia-Ukraine War that lasted more than a year. The embargo sanctions were mainly imposed on Russia's oil and gas exports, which provide Russia with its biggest revenue and ensure its military operations in Ukraine. However, the embargo sanctions did not effectively pressure Russia economically to change its military actions in Ukraine. Instead, Russia's oil and gas exports experienced a resilience that continued to ensure its military operations in Ukraine. This article discusses the resilience and relevance of Russia’s oil and gas exports to continuation of Russia's military operations toward Ukraine in February 2022 until October 2023 period. Russia’s military operations to Ukraine has been going more than one year despite the economic embargo sanctions imposed on Russia by the United States, the Europe Union, and their allies. While facing sanctions from the “majority of the world”, Russia's energy and economy is still resilient and ensured the continuity of the military operations. This article examines the dynamics of Russia’s energy export, specifically oil and gas, which have resilience from sanctions and embargoes, also the relevance to fund the military operations. This qualitative article is a contemporary historical study that also uses energy geopolitics approaches from Yu and Dai (2012), and political economy. Sources of data for the analysis of this article were collected from news media, statistical data, and reports of Russian and European petroleum agencies, which revealed that Russia's oil and gas exports fluctuated, making Russia's continuing involvement in the Russia-Ukraine conflict as well as its resilience during the embargo from its political opponents.